Unveiling the French Republic: national identity, secularism, and Islam in contemporary France - Nilsson, Per-Erik (Studies in critical research on religion, 2018)
The Islamic Veil Affairs (2003-4 and 2009-2011), which led to the banning of Muslim girls wearing Islamic headscarves in French public schools and women wearing full-face veils in public, have raised serious concerns about the relationship between secularism and the freedom of religious expression.00In this book, 'Unveiling the French Republic: National Identity, Secularism, and Islam in Contemporary France', Per-Erik Nilsson engages in a careful critical analysis of the Veil Affairs. His critique, for the most part, is not on the decision of Muslim women to wear the veil but rather on the misuse of secular ideology to justify religious intolerance and mask ethnic prejudice